Hedonic test of moringa leaf sago cookies with the addition of Balinese complete seasoning - Oryza Armabela; Risa Panti Ariani; Ni Made Suriani (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to determine the formulation of moringa leaf sago cookies with the addition of Balinese complete seasoning and public acceptance of the product through organoleptic preference tests based on aspects of taste, aroma, texture, and color. The type of research used is quantitative with an experimental approach. To obtain data in the community, this study uses an observation method, namely by distributing the favorite test sheets to the consumer community. Then the data will be analyzed using descriptive statistics (mean). The results of the study showed that the addition of Balinese complete seasoning received a good response from the community according to taste with the category of very like, aroma with the category of very like, texture with the category of  very like and color with the category of  very like.